2021
DOI: 10.3390/genes12111691
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Interpretation of Anti-Aging Mechanisms for ω-3 Fatty Acids

Abstract: Aging is one of the hottest topics in biomedicine. Previous research suggested that ω-3 fatty acids have preventive effects on aging. However, most of previous studies on the anti-aging effects of ω-3 fatty acids are focused on clinical observations, and the anti-aging mechanisms of ω-3 fatty acids have not been fully elucidated. This stimulated our interest to use multi-omics data related to ω-3 fatty acids in order to interpret the anti-aging mechanisms of ω-3 fatty acids. First, we found that ω-3 fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Omega-3 PUFA can modulate platelet aggregation and hypertension [ 53 ] and protect against senile dementia [ 58 ]. Xie et al revealed that the human gut microbiome partially mediates the anti-aging mechanisms of omega-3 fatty acids [ 59 ].…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%
“…Omega-3 PUFA can modulate platelet aggregation and hypertension [ 53 ] and protect against senile dementia [ 58 ]. Xie et al revealed that the human gut microbiome partially mediates the anti-aging mechanisms of omega-3 fatty acids [ 59 ].…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%
“…The intake of n-3 PUFA is also inversely related to the rate of telomere shortening, an important marker of cell aging [28][29][30]. In addition, lower levels of EPA and DHA are linked with an increased risk of cognitive impairment and dementia, making them a potential marker of brain aging [19,21,31,32]. It has also been suggested that circulating n-6 PUFA levels benefit cardiometabolic outcomes, although controversial findings remained [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%